Microplastic Morphotype Composition and Intra-Colony Distribution in tabulate Acropora at Labuan Beropa, Indonesia - Nurul Muslimah; Emiyarti Emiyarti; Laode Alirman Afu; Warsidah Warsidah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Microplastics can interact with coral surfaces and tissues, yet information on their distribution among structural sections of coral colonies remains limited. This study assessed microplastic morphotypes and abundance in tabulate Acropora colonies from Labuan Beropa waters, South Konawe, Indonesia. Sampling was conducted at two stations representing a densely inhabited fishing area and a site influenced by a river mouth and fishing vessels. Fifteen colonies were selected at each station, and paired 4-cm fragments were collected from the colony tip and near the basal section, producing 60 samples. Organic material was digested using 10% KOH, filtered through Whatman No. 42 paper, and visually examined under a binocular microscope at 40x magnification. Four suspected microplastic morphotypes were recorded: fiber, fragment, film, and foam. Fiber was the dominant morphotype in all station-section combinations. The highest abundance was recorded at the colony tip of Station II (21.2 particles individual-1), whereas the lowest was foam at the same station and section (0.5 particles individual-1). Descriptively, total abundance was higher at colony tips than near the basal sections at both stations. Water temperature was 30 degrees C, salinity was 31 ppt, and current velocity ranged from 0.05 to 0.07 m s-1. The results indicate non-uniform intra-colony distribution and suggest that riverine inputs, domestic activities, and fisheries may contribute to particle exposure. Polymer confirmation, contamination blanks, and paired statistical analyses are recommended for future studies.